Strategi Komunikasi Kepala Sekolah dalam Membangun Iklim Organisasi Kondusif : Studi Kasus di SMK Fadilah Tangerang Selatan - Indah Marita Sari; Maria Silvia Rahman; Okke Rosmaladewi (Lembaga Teewan Journal Solutions, 2026)
The principal's communication strategy plays a crucial role in creating a conducive organizational climate in educational institutions. This study aims to analyze the principal's communication strategy in fostering a positive organizational climate at SMK Fadilah South Tangerang. A qualitative approach with a case study design was employed. Data were collected through in-depth interviews, observations, and documentation involving the principal, teachers, and education staff, and analyzed using the interactive model of Miles, Huberman, and Saldaña with source, technique, and time triangulation to ensure data validity. The findings reveal that the principal applies two complementary communication patterns, namely formal communication through meetings, official circulars, and policy dissemination, and informal communication through direct discussions, interpersonal interactions, and digital communication platforms. The integration of these communication strategies enhances work coordination, information transparency, teacher participation in decision-making, and collaborative relationships within the school. Nevertheless, challenges remain, including delays in information dissemination and unequal participation among school members. The study concludes that an integrated communication strategy serves as an essential instrument of transformational leadership and contributes significantly to the development of a conducive organizational climate in vocational schools.